2022
DOI: 10.1097/qad.0000000000003202
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled HIV and inflammation is associated with intracranial saccular aneurysm presence

Abstract: Objective:To study biomarkers of inflammation in cerebrovascular disease, exploring modifiable and non-modifiable biochemical and clinical risk factors associated with the presence of intracranial saccular aneurysms (ISAs) in an HIV-positive cohort.Design:A cross-sectional community-based study was used to study blood biomarkers of inflammation as predictors of cerebrovascular disease, specifically the presence of ISAs in persons with HIV. Potential biochemical and clinical predictors of ISA presence were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…A recent cross-sectional study reported a correlation between the presence of several cytokines and incidence of intracranial saccular aneurysms in uncontrolled HIV patients. 11 Further, prior studies have reported the presence of leukocytoclastic vasculitis in extracranial aneurysms in HIV patients. 12 Future research is needed to examine these potential pathophysiologic mechanisms, including pathologic exam of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…A recent cross-sectional study reported a correlation between the presence of several cytokines and incidence of intracranial saccular aneurysms in uncontrolled HIV patients. 11 Further, prior studies have reported the presence of leukocytoclastic vasculitis in extracranial aneurysms in HIV patients. 12 Future research is needed to examine these potential pathophysiologic mechanisms, including pathologic exam of intracranial aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Comfort nursing from the perspective of high-quality nursing is a holistic, individualized, creative and effective nursing model. [5][6][7] This study compared the effects of comfort nursing and routine nursing on the postoperative rehabilitation progress of patients with intracranial aneurysms from the perspective of high-quality nursing, and discussed the nursing effect of comfort nursing on patients with intracranial aneurysms from the perspective of high-quality nursing.…”
Section: Introductionmentioning
confidence: 99%